PECULIARITIES OF SPEECH DEVELOPMENT IN INFANCY OF A NORMALLY DEVELOPED CHILD - The daughter of Aralova Iroda Melikozi; Nishonova Durdona (Academia Science Repository, 2023)
All the reforms implemented in our country are aimed at raising a healthy and well-rounded generation. Peculiarities of speech development in infancy of a normally developed child. Developmental periods of speech skills